Comparison between 2D and 3D magnification factor of non-load-carrying fillet welded joints - Xu, Chenxiang. (2010)
This project aims to investigate the stress intensity factor for surface cracks of several double T-butts models. The project is consisted by three main phases. Phase 1 of the study involves the boundary element modelling of a simple 3-D model using AutoCAD. After extracting all relative parameters including the sequence of the eight nodes in the elements and the coordinates of the nodes, the BEM_J.exe is used as the numerical solver to calculate the stress intensity factors values. The results of stress intensity factors generated from the boundary element method were then compared towards the calculated stress intensity factor using the exact solution formula and finally calculate the Mk. Phase 2 of this project includes writing a C program to extract the parameters instead of doing manually as same as in phase 1, so that the left complex models can be analysed in a short time. Phase 3 will be the main phase of this project. After generating the C program, 3 batches of models will be tested. Models are categorized according to the relationship between the crack length and the plate thickness. The effect of weld leg length to the stress intensity factor will be studied after the test. The objective of 2D approximation compared to 3D modelling solutions is compared after all models are completed and the buffer and differences between the 2 is established. The stress intensity factors obtained from the double T-butt boundary element model demonstrated that the larger the thickness of the attachment plate, the larger magnitude of stress intensity factors. Furthermore, the stress intensity factors obtained from the test can be concluded to be well-agreeable compared with exact stress intensity factor obtain from the derived equations.